Impairment in dating and retrieving remote events in patients with early Parkinson's disease. Issue 4 (April 1997) - Venneri, A; Nichelli, P; Modonesi, G; Molinari, M A; Russo, R; Sardini, C
Abstract : Remote memory has been studied in a group of 25 non-demented patients with Parkinson's disease and their performance has been compared with that of 22 healthy control subjects. Only patients who scored > or = 27 on the mini mental state examination and with no anticholinergic treatment were included in the sample. A remote memory questionnaire was given, to evaluate memory for public events that occurred from 1966 to 1990. Each event was probed with five questions concerning its content and one for the date. Compared with healthy subjects, patients with Parkinson's disease were significantly impaired both in recalling the content and in dating remote events. These results support the claim that remote memory in patients with Parkinson's disease is disrupted independently of dementia. This impairment might result from a dysfunction at the level of the circuit connecting the basal ganglia to the frontal lobes.